Analisis Pemasaran Melalui Harga dan Promosi Home Industry Tahu 99 Kennata Arjo Mukti di Kota Palangka Raya - Merisa Oktaria; Revnussa Octobery; Windy Utami Putri; Wenny Awalina; Elsa Criscya Monika; Tonich Uda (FKIP, Universitas Palangka Raya, 2023)
Competition between companies is not only in terms of product types and product quality but from the company's strategy in setting prices and promotions and how to set prices and promotions used so as to increase consumer buying interest. Companies that are able to compete are companies that have a competitive advantage, where the company can carry out pricing and promotion strategies appropriately. Therefore, companies must act quickly and actively in marketing products and setting prices according to products, promotions that can attract consumers. Appropriate pricing and promotion strategies with the aim that consumers do not switch to competing products. The purpose of this study is to describe the pricing and promotion strategy of the Home Industry Tofu 99 Kennata Arjo Mukti in Palangka Raya City. This type of research is qualitative research. This study involved 10 (ten) informants. The data taken in this study is to make observations first, then conduct interviews, and document the data needed, then analyzed qualitatively including data reduction, presenting data, and drawing conclusions. The results showed that: Home Industry tofu 99 Kennata Arjo Mukti set prices based on market prices. The promotion used is by placing a banner in front of the production site, and promotion through word of mouth to another. Home Industry Tofu 99 Kennata Arjo Mukti sets the price according to the quality of the product, which is delicious, does not use preservatives, the ingredients used do not contain harmful ingredients such as formalin and borax. In promoting the information submitted in accordance with the condition of the product being sold. Home Industry Tofu 99 Kennata Arjo Mukti has two types of tofu pieces, namely medium-sized tofu and large-sized tofu with the same taste.